2011
DOI: 10.1111/j.1528-1167.2011.03115.x
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of adenosine kinase in astrocytes in experimental and human temporal lobe epilepsy

Abstract: Purpose Adenosine kinase (ADK) represents the key metabolic enzyme for the regulation of extracellular adenosine levels in the brain. In adult brain, ADK is primarily present in astrocytes. Several lines of experimental evidence support a critical role of ADK in different types of brain injury associated with astrogliosis, which is also a prominent morphological feature of temporal lobe epilepsy (TLE). We hypothesized that dysregulation of ADK is an ubiquitous pathological hallmark of TLE. Methods Using immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
119
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 131 publications
(130 citation statements)
references
References 37 publications
8
119
1
Order By: Relevance
“…However, a subsequent high, acute Ado concentration promotes glial activation and astrogliosis, one of the relevant features of the epileptic brain [153], via stimulation of A 2A receptors [154,155]. The expression of ADK by glial fibrillary acidic protein (GFAP)-positive astrocytes and the overexpression of ADK in parallel with the formation of astrogliosis has been observed [27,65,93,156]. Additionally, although A 1 receptors may reduce astrogliosis [157], expression of astrocytic A 1 receptors may be reduced by epileptogenesis [158][159][160][161].…”
Section: Modulation Of Adenosine Levels and Epileptic Activity By Metmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a subsequent high, acute Ado concentration promotes glial activation and astrogliosis, one of the relevant features of the epileptic brain [153], via stimulation of A 2A receptors [154,155]. The expression of ADK by glial fibrillary acidic protein (GFAP)-positive astrocytes and the overexpression of ADK in parallel with the formation of astrogliosis has been observed [27,65,93,156]. Additionally, although A 1 receptors may reduce astrogliosis [157], expression of astrocytic A 1 receptors may be reduced by epileptogenesis [158][159][160][161].…”
Section: Modulation Of Adenosine Levels and Epileptic Activity By Metmentioning
confidence: 99%
“…Additionally, although A 1 receptors may reduce astrogliosis [157], expression of astrocytic A 1 receptors may be reduced by epileptogenesis [158][159][160][161]. A 2A receptors are upregulated by high Ado levels [27]; thus, the crucial role of Ado receptor expression in astrogliosis, the astrogliosisinduced increase in ADK activity and the disruption of Ado homeostasis have been suggested in epilepsy [151,156,162,163]. It was concluded that (i) upregulation of ADK in chronic epilepsy mainly occurs in astrocytes via Adoreceptor-induced astrogliosis in the adult brain, (ii) high ADK activity in astrocytes results in a decrease of Ado concentration, which may induce chronic recurrent seizures, (iii) consequently, ADK may be the link between astrogliosis and neuronal dysfunction in epilepsy and (iv) astrogliosis and concomitant epileptic seizures may be prevented by Ado receptor modulation [65,93,164,165].…”
Section: Modulation Of Adenosine Levels and Epileptic Activity By Metmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental researches demonstrate that overexpression of ADK per se might be sufficient to trigger electrographic seizures [8,15,18,19,22]. Clinical evidence also demonstrates that ADK as a common pathologic hallmark and a target for treatment in intractable epilepsy such as temporal epilepsy [8,9], tumor-Overexpression of Adenosine Kinase in Patients with Epilepsy Associated With Sturge-Weber Syndrome related epilepsy [11], Rasmussen encephalitis [10,24], and focal cortical dysplasia [12].…”
Section: Discussionmentioning
confidence: 99%
“…Chronic ischemia in the cortical areas affected by leptomeningeal angiomatosis has been usually considered to be the epileptogenic mechanism [7]. Increasing clinical evidence from specimen surgically resected from patients with drug-resistant epilepsy, including temporal lobe epilepsy [8,9], Rasmussen encephalitis [10], astroglial tumorrelated epilepsy [11], and focal cortical dysplasia [12], demonstrated that overexpression of astroglial adenosine kinase (ADK) contributing to seizures generation in human chronic epilepsy. However, in our study, it is first time to literarily report a link between adenosine and SWS.…”
Section: Immunohistochemistrymentioning
confidence: 99%